Functionality and coexistence of Spanish and Basque in Bilbao’s linguistic landscape - Fernández Juncal, Carmen (Íkala, Revista de Lenguaje y Cultura, 2020)
Spanish and Basque have lived together for centuries with different degrees of permeability and complementarity depending on the physical and temporal environment in which this coexistence takes place. The present study, of a mixed, quantitative and qualitative nature, examines the current linguistic landscape of Bilbao in order to determine the different functions assumed by Spanish and Basque in a territory where majoritary use of Spanish alternates with a very active policy of promoting Basque. Based on a corpus of images with public texts, a process of classification of the linguistic signs according to different parameters was carried out. The quantitative analysis highlights the minoritary presence of Basque in relation to Spanish, as a reflection of the use of these two varieties in the same area. There is also a division of functions between the two: greater informative-denotative function for Spanish and greater symbolic-connotative functionfor Basque. This situation calls for a reconsideration of the traditional roles between majority languages and minority languages.